Rhabdomyosarcoma arising in transgenic mice harboring the beta-globin locus control region fused with simian virus 40 large T antigen gene. - Teitz, T (1993)
The beta-globin locus control region (LCR) confers a high level of erythroid-specific and copy-number-dependent expression to human globin genes in transgenic mice. Simian virus 40 T (tumor) antigen (Tag) with its own natural enhancer causes choroid plexus tumors in mice. We investigated the effect of the LCR on Tag gene expression, reasoning that mice harboring a LCR-Tag fusion gene might develop hematopoietic malignancies. To test this hypothesis we introduced an enhancerless Tag gene downstream of a LCR cassette into the germ lines of mice. The phenotypes of the transgenic mice depended on the copy number of the transgene. While mice with 1-2 copies matured normally, those with 3-7 copies developed rhabdomyosarcomas in different anatomic sites at high frequency and showed hyperplasia of the pancreatic islet cells which progressed to pancreatic islet tumors. In addition, the mice bearing 7 copies of the transgene had hypoglycemia and were stunted in growth. Mice with more than 10 copies were markedly stunted in growth and died within 2-4 weeks. Tag expression was detected at high levels in the mouse tumors but not in any other tissues, including the hematopoietic cells.